Lateral impact of tubular structure - theoretical and experimental analysis. Pt.1 - Investigation of single tube. - Lipa, Sebastian; Kotełko, Maria (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2013)
If a thin-walled member is subjected to dynamic load, the estimation of its structural behaviour has to count for the strain-rate influence upon stress-strain material characteristics. It is particularly important when a thin-walled member works as an energy absorber. In the paper, the problem of collapse load, post-failure behaviour and energy dissipation of a tubular structure subjected to lateral impact load is presented. The analytical solution of the problem of initial collapse load and post-failure behaviour of a single tube is discussed. The analysis is limited to the “dynamic progressive crushing”, which means that we take into account the strain-rate but neglect inertia effects. The solution is based on the yield-line analysis and takes into account the impact velocity and strain rate, using the Cowper-Symonds constitutive relation. The same problem concerning both the single tube and multi-member tubular structure subjected to lateral bending impact load is solved using Finite Element (FE) simulation, which also takes into account the impact velocity and strain rate, using the corresponding to Cowper-Symonds Perzyna material model. Results of numerical calculations are compared with those obtained from the quasi-dynamic tests performed at different loading velocities on single tubes. The results are shown in load-deformation diagrams and diagrams of deformation patterns.
Keywords: tubular structure; lateral bending; impact load; strain rate; zginanie boczne; wpływ obciążenia; szybkość odkształcania; obliczenia numeryczne; konstrukcja rurowa